Surgical treatment of axillary artery aneurysms through a transaxillary approach - Francesca Palma; Giuseppe Asciutto; Martin Austermann; Marco Virgilio Usai (Angiologia e Cirurgia Vascular, 2023)
BACKGROUND: Axillary artery aneurysms are rare. Due to their anatomical peculiarities, their therapeutic management is individualized. Minimal invasive endovascular treatments are gaining increased popularity. However, surgical solutions are associated with better long-term patency.